(untitled) (De Legibus - Law Journal, 2022)
In times of pre-insolvency, the director’s conduct should be oriented towards the restructuring of enterprises, which mainly requires the fulfilment of a special duty to promote the negotiation of a restructuring plan. This special duty exists if the restructuring plan is necessary, adequate, reasonable, and fair to the dissenting and affected parties. According to this, it is important to ensure that affected and dissenting parties cannot unreasonably prevent the adoption of restructuring plans that would bring the debtor enterprise back to viability, satisfy the best-interest-of-creditors’ test, and ensure they are treated at least as favourably as any other class of the same rank and more favourably than any junior class.